CONSERVATION OF GYMNOSPERM SPECIES IN YEN TU NATIONAL FOREST, QUANG NINH PROVINCE - Thanh Lam, Phan; Van Sam, Hoang; Cong Anh, Dao; Thi Tuyet, Nguyen; Phuong Thao, Nguyen; Khanh Nhu, Tran; Matusch, Tobias (Journal of Forestry Science and Technology, 2016)
This paper surveys the Gymnosperm species in Yen Tu National Forest, Quang Ninh province. A total of 15 Gymnosperm species were found in Yen Tu National Forest belonging to the 5 families Podocarpaceae, Cupressaceae, Cycadaceae, Pinaceae and Gnetaceae. Gymnosperm species in Yen Tu National Forest have a high conservation value with all 15 species listed in IUCN (2015), 02 species in Viet Nam red data book (2007) and 03 species are listed in Decree 32/2006 of the Vietnamese government. The majority of gymnosperms species at Yen Tu National Forest are distributed from 200 to 600m above sea level. Juniperus chinensis L. and Juniperus squamata Buch. - Ham. are distributed up to 800m; Podocarpus chinensis (Roxb.) Wall. and Podocarpus pilgeri Foxworthy are distributed up to 1000m. Only Nageia fleuryi (Hickel) de Laub are distributed at lower than 400m above sea level. This research also provides the morphological and ecological characteristics of Podocarpus pilgeri Foxworthy and Dacrydium elatum (Roxb.) Wall. ex Hook in the research area.